«The socialist parties in Iberia, before and after the Great Recession, with some insights from Greece and Italy» - Freire, A. (Seminar «Perspektiven der Sozialdemokratie in Europa», 2021)
André Freire (2021) «The socialist parties in Iberia, before and after the Great Recession, with some insights from Greece and Italy», 12-05-2021, (7 p.m. Central European Time; 6 p.m. GMT Lisbon Time), Invited Keynote speaker at the Seminar «Perspektiven der Sozialdemokratie in Europa», Chaired by Professor Hans-Dieter Puhle, University of Frankfurt, Forschungskolleg Humanwissenschaften der Goethe-Universität in Kooperation mit der Werner Reimers Stiftung available in youtube, after livestream: https://www.youtube.com/watch?v=w1QNMpoEgr4